2017
DOI: 10.20517/2394-5079.2017.06
|View full text |Cite
|
Sign up to set email alerts
|

MELD score and AST-to-platelet ratio index predict long-term survival in patients with a small hepatocellular carcinoma following non-transplant therapies: a pilot study

Abstract: Aim Liver transplantation (LT) is the most effective treatment for long-term survival from hepatocellular carcinoma (HCC); however, insufficient donors limit therapy. We sought to identify characteristics that predicted long-term survival after non-transplant therapies in patients with small HCC. Methods In a database of 1,050 HCC patients, we identified those with single HCC ≤ 3.0 cm, who underwent hepatic resection (HR, n = 16), radiofrequency ablation (RFA, n = 55), or LT (n = 23) with 5-years follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…18 Sarkar et al reported that AST-to-platelet ratio index (APRI) was the strongest predictor of OS after radical surgery by liver transplantation or RFA for small HCC. 19 Thus, the previous reports showed that AST was an important predictor for OS. The reason why platelet count and albumin level were not extracted as the predictor by multivariate analysis in our study appears to be correlated with the relative short observation period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18 Sarkar et al reported that AST-to-platelet ratio index (APRI) was the strongest predictor of OS after radical surgery by liver transplantation or RFA for small HCC. 19 Thus, the previous reports showed that AST was an important predictor for OS. The reason why platelet count and albumin level were not extracted as the predictor by multivariate analysis in our study appears to be correlated with the relative short observation period.…”
Section: Discussionmentioning
confidence: 97%
“…Nishikawa et al showed that AST and Child‐Pugh score were predictors for OS in patients with HCC receiving sorafenib by multivariate analysis 18 . Sarkar et al reported that AST‐to‐platelet ratio index (APRI) was the strongest predictor of OS after radical surgery by liver transplantation or RFA for small HCC 19 . Thus, the previous reports showed that AST was an important predictor for OS.…”
Section: Discussionmentioning
confidence: 99%
“…27 A previous study indicates that the AST-to-platelet ratio index can be used to predict long-term survival in patients with HCC following non-transplant therapies. 28 Furthermore, ALB is proved to be differentially expressed between tumor cells and non-tumor cells of patients with HCC. 29 A previous study proves that ALB is a predicator for patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple factors that could affect the malignancy and progression of HCC including tumor number, size, and macrovascular invasion, which are evaluated by radiological imaging before treatment [8]. Prognosis is also affected by the degree of hepatic dysfunction, patient comorbidities, and tumor biology [9]. Recently, the French study group for liver transplantation reported on a new predictive model for HCC recurrence, called the alpha-fetoprotein (AFP) model.…”
Section: Introductionmentioning
confidence: 99%